If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -120 = 4b Solving -120 = 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. -120 + -4b = 4b + -4b Combine like terms: 4b + -4b = 0 -120 + -4b = 0 Add '120' to each side of the equation. -120 + 120 + -4b = 0 + 120 Combine like terms: -120 + 120 = 0 0 + -4b = 0 + 120 -4b = 0 + 120 Combine like terms: 0 + 120 = 120 -4b = 120 Divide each side by '-4'. b = -30 Simplifying b = -30
| -4.5-5.8= | | 12x^3+20x^2-x-6=0 | | 27+k=56 | | (x^2-5)(2x^2+3)= | | 9f+7=8f | | 120+110=180 | | 3v+3=5v+7 | | 3(5x+2)=51 | | -3-6x= | | 5n-3+n+9=24 | | 4x^2(3x^2+1)=0 | | 1s+2s+6+45-5=148 | | 1.7-(-3.8)= | | 5+4(x-1)=7x | | .125(16x-24)=2x-3 | | 4(2b-4)=(3-5b) | | 6+0.1x=0.15x-8 | | 64=20-4x | | 10-1.5x=16 | | 15-3v=-3(v-5) | | 2x-36=60-6x | | 14x+4x=2y | | 5+25+7=28 | | -12+5x=3x-8 | | 9=4m-7 | | (7x+4)=2 | | -2x+x+10=6-(2x+3x-8) | | -3(6-5a)=9a+24 | | factorx^2+6x-27=0 | | -2(4t-4)+5t=8t-5 | | y+2y-12=3 | | (w+6)(w-1)+(12w+7)(w-1)=0 |